Koncentracja produkcji i poziom wykształcenia a znajomość i przestrzeganie wybranych zasad bezpieczeństwa pracy w gospodarstwach mlecznych - Wysokiński, Marcin; Kosędka, Izabela (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2015)
The article concerns farmers’ knowledge and compliance of principles of safe and hygienic work in dairy farms. Surveyed objects were grouped by the level of farmer’s education and the number of cows in the herd. It has been shown that there is quite a significant correlation between the level of farmer’s education on one hand and their understanding and compliance with health and safety regulations on the other.